Indonesian Worker Protection from Labour Exploitation in Singapore - Mety Rahmawati (Faculty of Law, Universitas Jenderal Soedirman, 2019)
Since 2017, Indonesian labour in Singapore has been getting a salary of SGD 550 excluding the compensation for overtime work. It has attracted Indonesian citizens to work in Singapore. However, they experience exploitation from their employers and, based on the survey, they work over time, receive low salaries and a little time off even some of them experience physical or verbal abuse. The regulations issued by Indonesia have not been able to protect the rights of its migrant workers in Singapore. This is due to the weakness of legal enforcement. To get the protection, the victims require long and strenuous efforts. This is very aggravating for Indonesian labour, considering they are in a state of fear. Indonesian government should learn from the experience of the Philippines, in which the sender of the labour is the government of the Philippines which has been recognized by ILO.Keywords: Protection, Indonesian labour